2020
DOI: 10.3390/cancers12051129
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Agents Sensitize Resistant Cancer Cells to the DR5-Specific Variant DR5-B More Efficiently Than to TRAIL by Modulating the Surface Expression of Death and Decoy Receptors

Abstract: TRAIL is considered a promising antitumor agent because it causes apoptosis of transformed cells without affecting normal cells. However, many types of tumors are cytokine resistant, and combination therapy with various chemotherapeutic drugs is being developed to overcome the resistance. We have demonstrated that the combination of TRAIL with doxorubicin, bortezomib, and panobinostat dramatically reduced the viability of TRAIL-resistant A549 and HT-29 cells. Chemotherapy even more efficiently sensitized cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…It was demonstrated that the DISC formed by DR5-B did not contain DR4 receptor in the HT-29 and PANC-1 cell lines, while in the DISC formed by TRAIL both DRs were detected. However, DR4 internalization by DR5-B was observed earlier after strong upregulation of the surface DRs by chemotherapeutic agents ( Artykov et al, 2020 ). Obviously, increased expression of death receptors on the cell surface promotes the formation of heterodimers where the receptors can be internalized together as part of the same DISC ( Szegezdi et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the DISC formed by DR5-B did not contain DR4 receptor in the HT-29 and PANC-1 cell lines, while in the DISC formed by TRAIL both DRs were detected. However, DR4 internalization by DR5-B was observed earlier after strong upregulation of the surface DRs by chemotherapeutic agents ( Artykov et al, 2020 ). Obviously, increased expression of death receptors on the cell surface promotes the formation of heterodimers where the receptors can be internalized together as part of the same DISC ( Szegezdi et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The selectivity of the cancer cells to TIC10 and TRAIL-inducing compounds relies on the overexpression of DR4 and DR5 compared to non-cancerous cells [ 37 , 38 ]; thus, these compounds are promising targeted drugs. In earlier studies, it was reported that BOZ could enhance the expression of these death receptors (DR4 and DR5) [ 20 , 21 , 39 ]. As it was proposed, our results confirm these previous findings as increased surface receptor expression of DR5 was detected after BOZ and BOZ+TIC10 treatments in the investigated A2058 melanoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it was demonstrated that BOZ could enhance the expression of proteins, e.g., DR4 or DR5, in HT-29 human colorectal adenocarcinoma cells, in A549 human lung adenocarcinoma cells and in human non-small cell lung cancer cells [ 20 , 21 ]. We hypothesized that following a co-treatment with BOZ and TIC10, the enhancement in the expression of the TRAIL protein post-TIC10 treatment and the upregulation of the death receptors post-BOZ treatment could lead to reduced cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the anti-tumor activity of MSC-TRAIL against lung cancer, specifically in pre-clinical models of NSCLC [ 48 , 49 , 50 ]. However, the characteristic of TRAIL resistance has been observed in some of the NSCLC cell lines, indicating that not all the NSCLC subtypes would benefit from MSC-TRAIL treatment [ 51 , 52 ]. In this study, we have shown for the first time that chemo-sensitization of the NSCLC cell lines and their CSCs, particularly the CD133+ population, using first-line chemotherapies such as cisplatin, 5-FU and vinorelbine was able to enhance the anti-tumor effect of MSC-TRAIL.…”
Section: Discussionmentioning
confidence: 99%